Infentarisasi Hawar Daun pada Jagung di Desa Suka Menang, Kecamatan Gelumbang, Muara Enim - Ramadona, Diva; Gunawan, Bambang; Kurnia, Fitra Nanda; Valentine, Dinda Putri; Ganda, Ganda; Ahmad, Mytha; Norarita, Yollan; Nurasni, Serli (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2023)
Ramadona, D., Gunawan, B., Kurnia, F. N., Valentine, D. P., Ganda, G., Ahmad, M., Norarita, Y., & Nurasni, S. (2023). Infentarization of leaf blight in maize in Suka Menang Village, Gelumbang Subdistrict, Muara Enim. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang 21 Oktober 2023. (pp. 237-251). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Maize (Zea mays L.) is one of the food commodities that has an important role in Indonesia after rice and has considerable market opportunities. This study aimed to determine the control of leaf blight in corn plants in Suka Menang village, Gelumbang sub-district, Muara Enim district, South Sumatra. Data collected included the type of disease that attacked and its intensity. The results of the research obtained from 5 farmers' fields in Suka Menang village, Gelumbang District, Muara Enim Regency, namely the highest level of disease, were found on Mrs. Watini's land (58.00%), Mr. Manijo's land (37.50%), and Mr. Supriyadi's land (15.50%). In plant maintenance on five corn fields, there are farmers who carry out plant maintenance, such as weeding, and some do not. Farmers who do weed have different frequencies. The control carried out by farmers in Suka Menang Village, Gelumbang Subdistrict, Muara Enim Regency combines technical culture control with intercropping, variety selection, and chemical control with pesticides. Results of this study indicate that corn farmers in Suka Menang Village, Gelumbang District, and Muara Enim Regency have mostly controlled leaf blight on corn plants. Maize farmers in Suka Menang village have used vegetable pesticides but the effects are long-lasting so according to farmers, it is not effective enough to fulfill such consumer demands. Therefore, farmers inevitably still use chemical pesticides even though they have to pay additional costs. In addition, the reason chemical pesticides are still used is because of the pressure from consumers who want good and smooth corn yields and a lot of demand. So, the conclusion of this study is that indirectly the behavior of farmers in cultivation has carried out the components of integrated disease control on the five corn fields including crop rotation, land sanitation, variety selection, balanced fertilization, technical culture and others.